Engine Performance And Smoke Emission Tests Of Transesterified Swietenia macrophylla King (Philippine Broad-Leaved Mahogany) Seed Oil - Jeremy James E. Ogilvie; Claudette Miracel R. Oñate; Gemarie Hazel F. Quetua; Maria Natalia R. Dimaano (ASEAN Journal of Chemical Engineering, 2018)
Biodiesel is the most common alternative fuel that can be used in diesel engines. Commercially 2% of coco methyl ester (CME) as biodiesel is blended with petroleum based diesel and is used as fuel. Exhaust emissions are improved using the biodiesel blends. This study is devoted to the engine performance test of diesel engine as affected by Mahogany Methyl Ester (MhME). The MhME was produced by extracting the oil of the mahogany seeds by solvent extraction using petroleum ether. Sulfuric acid catalyzed esterification and potassium hydroxide- catalyzed transesterification were used for the MhME production. The fuel properties of the B5 and B50 biodiesel blends were determined. The kinematic viscosities of B5 and B50 were reported as 3.21, and 3.63 mm2/sec, respectively. The engine performance test was done on a Gunt Hamburg CT 110 Four-Stroke Diesel Engine. Results showed that B5 MhME obtained the highest power and highest torque at full fuel load. For the fuel consumption, pure commercial diesel was observed to have the lowest at 2500 and at 2750 rpm. In addition, B50 MhME emits less CO2, CO, hydrocarbon and O2.